HUBUNGAN MASJID DAN SEJARAH SOSIAL PENDIDIKAN ISLAM - Triayudha, Anna; Pramitasary, Rateh Ninik; Anas, Hermansyah Akbar; Mahfud, Choirul (State Institute of Islamic Studies (IAIN) Palu, 2019)
The growth and development of Islamic Education is inseparable from the growth of institutions. The Prophet made it happen by establishing institutions that had a role in developing and advancing Islamic education, one of which was a mosque. Research on the relationship of mosques with the social history of Islamic education is discussed by using descriptive qualitative methods that are oriented to literature review. This paper shows that in the early period of Islamic education, the Prophet provided exemplary by building and empowering mosques. The example of the Prophet continued with the Caliphs afterwards until the present era. The mosque was built by the Prophet from the Al Haram mosque located in Makkah, Quba Mosque located in Quba, Nabawi mosque located in Medina and so on. The role and function of the mosque at that time was as a place of prayer, a place of prayer, a place for discussion or deliberation, a meeting place to develop a war strategy and others related to the problems and needs of Muslims. From time to time, the role or function of the mosque has changed slightly. In essence, mosques are currently influencing the development of the social history of Islamic education in Indonesia.